The psychological consequences of COVID-19 on children’s world - Sinaei, Reza; Pezeshki, Sara; Yazdani, Mostafa; Sabzevari, Fatemeh; Hassas Yeganeh, Mehrnoush (Iranian Journal of Child Neurology, 2021)
Dear Editor-in-Chief The world’s countries are presently shaken by a novel member of the coronavirus family. Apparently, a very tiny creature has been commissioned to carry out a large mission. This issue causes us to experience a universal life-threatening condition that is changing the life framework for humans. It appears that humans are showing a more real picture of themselves in the current turmoil.